2019
DOI: 10.1080/13625187.2019.1581164
|View full text |Cite
|
Sign up to set email alerts
|

Perfect- and typical-use effectiveness of the Dot fertility app over 13 cycles: results from a prospective contraceptive effectiveness trial

Abstract: Objective: Dynamic Optimal Timing (Dot) is a smartphone application (app) that estimates the menstrual cycle fertile window based on the user's menstrual period start dates. Dot uses machine learning to adapt to cycles over time and informs users of 'low' and 'high' fertility days. We investigated Dot's effectiveness, calculating perfect-and typical-use failure rates. Methods: This prospective, 13 cycle observational study (ClinicalTrials.gov NCT02833922) followed 718 women who were using Dot to prevent pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Li et al 21 describe several simulation studies using this method to estimate its efficacy in preventing pregnancy. Jennings et al 16 presents the findings from a prospective 13-cycle contraceptive effectiveness trial. At the time of writing, the Dot app has not received either European certification or FDA approval and some concerns have been expressed within the press about the marketing of the app to prevent pregnancies 33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Li et al 21 describe several simulation studies using this method to estimate its efficacy in preventing pregnancy. Jennings et al 16 presents the findings from a prospective 13-cycle contraceptive effectiveness trial. At the time of writing, the Dot app has not received either European certification or FDA approval and some concerns have been expressed within the press about the marketing of the app to prevent pregnancies 33…”
Section: Resultsmentioning
confidence: 99%
“…Five hundred (n=500) records did not meet the inclusion criteria. Nineteen papers were initially identified for inclusion, but one was rejected since it reported interim data from a study which was then published in full 2 months later 16. Eighteen (n=18) records met the criteria for inclusion and are examined in this scoping review (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This app uses date of menses and a proprietary algorithm to calculate fertile days. A one‐year study of over 700 DOT users found a typical use failure rate of 5.8% (95% CI, 3.6% – 8.1%) 11 . The DOT website currently shows that the standalone app is no longer available.…”
Section: What Should Clinicians Tell Their Patients About the Use Ofmentioning
confidence: 99%